Private and public spheres casted adrift by technology. Remarks on the historical building of subjectivity - Protzel, Javier (2009)
From a long-term outlook, the shaping of subjectivity is a historically meaningful matter. It has been unfolded throughout different periods according to different patterns of knowledge and sensitive perception. Intimacy is closely intertwined with secularization, as the releasing of the inner self has been inversely proportional to the fall of the ruling characters of the greater metanarratives. From gods to heros, from realistic novel characters to film fiction, and from there to the contemporary anti-hero, becoming finally oneself the narrator of one’s own life.